Student-Centered Pedagogies in Taekwondo: Redesigning Learning Models in Higher Education - Atika Swandana; Aditya Trinanda; Edwin Wahyu Dirgantoro; Muhammad Reza Destya; Nadhira Yasmine Ahmad (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2026)
Introduction: Traditional instructor-centered approaches in martial arts education often limit student autonomy and critical thinking development. This study examined the implementation of student-centered pedagogies in Taekwondo instruction within higher education settings. Purpose of the Study: To evaluate the effectiveness of student-centered learning models compared to traditional teaching methods in developing technical proficiency, tactical knowledge, self-efficacy, and autonomous learning behaviors among physical education students enrolled in Taekwondo courses. Materials and Methods: A quasi-experimental pre-post design was employed with 64 physical education students at Universitas Lambung Mangkurat, Indonesia. Participants were divided into experimental (n=32, student-centered pedagogy) and control groups (n=32, traditional instruction). The intervention spanned 14 weeks (28 sessions). Measurements included technical skill assessments, tactical knowledge tests, self-efficacy scales, and autonomous learning questionnaires. Data were analyzed using paired t-tests, independent t-tests, and ANCOVA (p<0.05) via SPSS version 26.0. Results: The student-centered group demonstrated significantly greater improvements in technical proficiency (d=1.24, p<0.001), tactical knowledge (d=1.46, p<0.001), self-efficacy (d=1.38, p<0.001), and autonomous learning behaviors (d=1.52, p<0.001) compared to the control group. Post-intervention between-group comparisons revealed substantial differences favoring the experimental approach across all measured variables. Conclusions: Student-centered pedagogies significantly enhance learning outcomes in Taekwondo education beyond traditional methods. Implementing autonomy-supportive, inquiry-based, and collaborative learning strategies promotes deeper engagement, skill development, and self-regulated learning capacities. These findings advocate for pedagogical reform in martial arts instruction within higher education contexts.